Learning about Corpora, Learning with Corpora - Grčić, Larisa; Brkić Bakarić , Marija (Corpora in Language Learning, Translation and Research: Proceedings of the International Conference Corpora in Language Learning, Translation and Research held at the University of Zadar (August 23–24, 2023), 2025)
Integrating corpora in university education has not been an easy task and still represents a major challenge. Despite the acknowledged advantages of the use of corpora in the realms of language teaching, translation, and research, the implementation of data-driven techniques and tools at university is very slow and partial. The aim of this paper is to offer an insight into the different ways in which corpora can be exploited in a high education environment, especially for language learning and translation.